Corruption and leadership in Africa: Evidence from Burkina Faso - (:unkn) unknown (My University, 2024)
This study assesses the role of a leader in anti-corruption fighting in Africa. It focuses on the rule of Thomas Sankara, one of the legendary figures of contemporary Africa.Using the synthetic control approach, we design a counterfactual for the actual Burkina Faso called "synthetic Burkina Faso" based on corruption before Sankara's tenure. The difference between Burkina Faso and Synthetic Burkina Faso highlights that the leadership of Thomas Sankara had a substantial effect in reducing corruption in Burkina Faso during his tenure over the period 1983-1987. This reduction effect in 1987 was as much as 70 percent of the 1982 level of corruption in the country. This result is robust to placebo tests. This finding highlights the leader's importance in shaping African countries' institutional trajectory. To fight corruption, having an exemplary leader is a cure.
Keywords: African Research